Research progress of tumor vaccines in the treatment of lung cancer - Zhang Jinpeng; Zhu Xiaoshan; Duan Jiangyi; Bu Jianxue; Ma Li (结直肠肛门外科)
Lung cancer is the leading cause of cancer-related death globally. Currently, lung cancer is mainly treated by radiotherapy, chemotherapy and surgery. Approximately 40% of patients are prone to relapse, and the survival rate in the advanced stages is less than 15%, indicating poor treatment outcomes. With the development of modern medicine, the emergence of immunotherapy has garnered widespread attention and importance in the medical community. In recent years, medical researchers at home and abroad have been actively engaged in the research of tumor vaccines, utilizing antigens to induce specific immune responses against lung cancer, achieving good clinical outcomes. This article provides a comprehensive review of the research progress in the treatment of lung cancer with tumor vaccines.